Morfologia da copa e crescimento de espécies arbóreas de cerrado em campo e em câmaras de topo aberto sob elevada concentração de CO2 - Melo, Nayara Magry Jesus (2020)
The Cerrado is a vegetation complex marked by climatic seasonality. It is savanna vegetation with the highest biodiversity in the world, the second-largest biome complex in South America, and the most significant hotspot in the Western Hemisphere. The degree of leaf deciduousness (deciduous, semideciduous, and evergreen) grouped Cerrado woody species. The intensity of the loss of foliage area is part of a strategy to cope with climatic seasonality in the Cerrado. Leaf deciduousness is interdependently related to other canopy characteristics such as architecture, branching pattern and bud content. On the other hand, there are significant differences in the responses of the canopy between woody species in the Cerrado to climate changes on our planet, such as the high concentration of CO2 [CO2]. One aim was to identify relationships between the content and development of aerial buds with the pattern of crown biomass allocation and seasonality. Another objective was to capture the influence of the elevation of [CO2] on the growth of Cerrado tree species in the initial growth phase. Through the following relationships, we seek to disclose possible functional groups of trees. We determined: (1) the composition and development of the aerial buds in 15 trees species with different patterns of leaf deciduity and relationship between bud development and climatic seasonality. (2) branch growth, leaf life span, and branching pattern in 15 trees species with distinct leaf deciduous patterns. (3) the influence of high atmospheric [CO2] and the vegetative growth and the allocation pattern biomass into roots, stems, and leaves of five tree species. The central hypothesis is that the permanence of the foliage would be a characteristic related to the structure of the crown evidenced by the morphological characteristics of shoots, the content of buds, and the responses of the species to the climatic changes. The deciduous species presented buds with preformed leaves surrounded by cataphylls and bud opening before the rainy season. The semideciduous ones presented buds with pre and neoformation of leaves. Only the semideciduous Eriotheca gracilipes K. Schum. had buds surrounded by cataphylls. The evergreen species showed buds with newly formed leaves, without the presence of cataphylls and bud opening after the beginning of the rainy season. The deciduous species presented plagiotropic branches with an of 35º. The majority of semideciduous and evergreen tree species had orthotropic branches with 60º and 61º, respectively. The deciduous species showed higher (p<0.05) speed of leaf expansion and shorter time of leaf and branch development concerning semideciduous and evergreen species. The leaf life span did not differ between the phenological groups. All deciduous, semideciduous, and evergreen species Miconia ligustroides (DC.) Naudin, Myrcia bella (Cambess.), Piptocarpha rotundifolia (Less.), and Schefflera macrocarpa (Cham. & Schltdl.) Seem. produced one branch order in growing season. Only evergreen Miconia albicans (Sw.) edified two orders of branching in the same growing season. Individuals of deciduous species Anadenanthera peregrina var. falcata (Benth.) e Tabebuia aurea (Silva Manso) Benth & Hook. F. ex. Moore under high [CO2] showed a significant increase (p<0.05) in dry mass of leaves and stem in relation to individuals under [CO2] ambient. Only deciduous T. aurea under high [CO2] showed a significant increase (p<0.05) in the relative growth rate. The species T. aurea (deciduous), Stryphnodendron adstringens Mart. (semideciduous) and Hymenaea stigonocarpa Mart. Ex Hayne. (evergreen) under high [CO2] showed shorter leaf expansion time and more prominent leaf expansion speed (except for H. stigonocarpa) about individuals under [CO2] ambient. The tree species groups were joited by bud pre-formation or neoformation, synchronic or continuous leaf producion, and plagiotropic or orthotropic shoots. It indicated the existence of at least three functional groups of tree species with different strategies for acquiring airspace. The increase in [CO2] made it possible to capture different strategies for capturing and using resources in the phenological groups, thus forming functional groups in Cerrado tree species.